Care Economy Migration and its Impact: A Review of Methodology of Related Studies - Dahal, Anita (Kalika Journal of Multidisciplinary Studies, 2025)
Care economy migration has become a significant global phenomenon, particularly affecting women from developing countries who migrate to high-income nations for employment in care-related sectors such as elder care, childcare, and domestic work. This paper critically examined the methodologies used in various studies on care economy migration and evaluates their effectiveness and limitations. The review highlights the role of different research approaches, including qualitative and quantitative methods, literature reviews, and policy analyses, in shaping our understanding of migration experiences, labor inequalities, and policy frameworks. Findings from the reviewed studies indicate that studies used literature reviews and policy analysis, in depth interviews and ethnographic methods to explore the lived experiences of migrant caregivers. In addition, some studies used quantitative methodologies to assess the economic valuation of unpaid care work and examined the migration decision making process through a multi-sited qualitative approach. While each methodology provides valuable insights, their limitations, including selection biases, lack of longitudinal analysis, and insufficient use of mixed-methods approaches, hinder a holistic understanding of care economy migration. Addressing these methodological gaps was crucial for developing a more comprehensive and equitable understanding of care economy migration